Clientelism and vote buying in local elections: A case study of Kartu Bintan Sejahtera - Tri Samnuzulsari; Wayu Eko Yudiatmaja (Faculty of Social and Political Science, Universitas Airlangga, 2018)
This study finds out clientelism and vote buying on Kartu Bintan Sejahtera (KBS) in Bintan Regency, Riau Islands. The objective of this study is to understand the practices of clientelism and vote buying using KBS. This study based on case study research. The informants consist of General Election Commission of (KPUD) Riau Islands, candidates of the governor of Riau Islands 2015-2020, candidates of Bintan Regent 2015-2020, along with their supporting parties and campaigning team, and bureaucracy of the implementation of KBS. The main findings of this study suggest that KBS is used as a clientelism and vote buying practices by the candidate of Riau Islands governor and Bintan Regent, 2015-2020 period. This study also finds that formal and informal political networks are utilized by the candidates as a clientelism and vote buying arenas. This study not only contributes to the literature of clientelism and vote buying, but also adds the literature of social policy in the context of Indonesian local politics setting. This study suggests that KBS is used as a media to obtain the support of the voters in the election of governor of Riau Islands and regent of Bintan 2015-2020. All candidates capitalize the issue of KBS to obtain the popularity. The patterns of the practice of clientelism and vote buying in KBS is by using various media campaigns to promote the success story of KBS. Not only in formal campaign but also in informal campaign, they always promote KBS as their success.